Application of Omnichannel Experience to Customer Loyalty though WOM Intention in the Beauty Industry: A Conseptual Framework - Sari, Mutiara Kusuma; Widodo, Arry; Rubiyanti, Nurafni; Silvianita, Anita (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study aims to analyze the effect of implementing an omnichannel experience strategy on customer loyalty with Word of Mouth (WOM) intention as a mediating variable. Customer data processed through various channels helps brands understand consumer preferences and behavior, so they can provide relevant and satisfying experiences. The results are expected to provide strategic insights for the beauty industry in building stronger relationships with customers, as well as increasing WOM intention that contributes to the purchasing decisions of others.